Humanitarian agencies and authoritarian states: A symbiotic relationship?. (22nd July 2013) - del Valle, Hernan; Healy, Sean
Abstract : The relationship between humanitarian agencies and authoritarian states is of growing concern to Médecins Sans Frontières (MSF), given the recurring difficulties experienced in negotiating access and implementing operations in such contexts. The effort to negotiate and gain approval from states to operate on their territory prompts reflection on the sources of legitimacy for action. Drawing on direct field examples in two countries only very rarely examined—Turkmenistan and Uzbekistan—this paper explores MSF's attempts to offer live‐saving medical care there. It shows that successful access negotiations hinged heavily on demonstrating added value (medical relevance) while simultaneously building relationships with authorities, identifying possible allies within health ministries, and hoping that such measures could promote a level of acceptance or trust needed to operate. It is clear that the operational space achieved is bound to remain limited and fragile, and that many compromises have to be considered and judged against ethical principles and the overall impact of the intervention.